2006
DOI: 10.1292/jvms.68.1105
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of GRA6 Genes from Toxoplasma gondii from Pigs in Okinawa, Japan

Abstract: ABSTRACT. Toxoplasma gondii from pigs in Okinawa Prefecture was characterized by nested PCR-restriction fragment length polymorphism (RFLP) and DNA sequence analysis of the dense granule antigen GRA6 gene. By nested PCR, parasite DNA was detected in 33 out of 91 lymph node samples with lesions similar to those found in toxoplasmosis samples that had been collected from pigs at an abattoir. RFLP analysis with MseI was successfully conducted in 29 of 33 PCR-positive samples to group the isolates into one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Another GRA6 allele was found in type x, a genotype described in Californian sea otters (10,42,43). More recently, Zakimi et al (57) found nine new sequences among 29 isolates from Japanese pigs. Most studies with GRA6 as a genetic marker have been conducted by PCR-RFLP (8, 14-20, 24, 43, 57).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another GRA6 allele was found in type x, a genotype described in Californian sea otters (10,42,43). More recently, Zakimi et al (57) found nine new sequences among 29 isolates from Japanese pigs. Most studies with GRA6 as a genetic marker have been conducted by PCR-RFLP (8, 14-20, 24, 43, 57).…”
Section: Discussionmentioning
confidence: 94%
“…The coding region of the GRA6 locus has been used as a marker for the genotyping of Toxoplasma (8, 15-20, 24, 33, 34, 40, 43, 47, 53). Sequencing of GRA6 detected a high degree of polymorphism (24,57). Single nucleotide polymorphisms (SNP) in the region encoding GRA6 can be detected by methods based on PCR followed by restriction fragment length polymorphism (PCR-RFLP): digestion of the amplification products with a single endonuclease (MseI) can differentiate genotypes I, II, and III (24).…”
mentioning
confidence: 99%
“…The highest number of strains originates from fattening pigs bred in outdoor farms. the world with types II and III predominant in Europe and North America (Mondragon et al 1998;Klun et al 2011;Dubey et al 2012;Turcekova et al 2013), and atypical strains more characteristic for South America and Asia (Zakimi et al 2006;Belfort-Neto et al 2007;Zhou et al 2010b;Bezerra et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that all isolates were type II by using 11 markers [ 20 ]. According PCR-RLFP of the GRA6 gene, the type I, II, and III of Toxoplasma were reported from pigs in Japan [ 34 ], the type II and III from humans, chicken, duck, and cat in Iran [ 23 ] and type II and III from humans in Cyprus [ 35 ].…”
Section: Discussionmentioning
confidence: 99%